Tren dan Efektivitas Model Flipped Classroom terhadap Kemampuan Berpikir Kritis Siswa Sekolah Dasar: A Systematic Literature Review - Ziadatul Maslikha; Putri Rachmadyanti; Ganes Gunansyah; Wasis Suprapto (Jurnal Ragam Pengabdian, 2026)
The Flipped Classroom model has become an increasingly popular pedagogical approach in elementary education, as it reallocates instructional time by shifting basic content delivery outside the classroom and dedicating in-class time to discussion, collaboration, and higher-order thinking activities. Given the growing number of studies examining this model, a comprehensive mapping of research trends and its effectiveness on students' critical thinking skills is needed. This study aims to map publication trends and analyze the effectiveness of the Flipped Classroom model in improving elementary school students' critical thinking skills. This study employed a Systematic Literature Review (SLR) method following the PRISMA 2020 protocol. Literature searches were conducted across the Scopus, Google Scholar, ERIC, ScienceDirect, and DOAJ databases for articles published between 2020 and 2026, yielding 28 eligible articles out of 312 initially identified. The results show a steadily increasing trend of Flipped Classroom research since 2022, dominated by studies from Indonesia using quantitative and Research and Development approaches. The Flipped Classroom model was consistently found to be effective in enhancing students' critical thinking skills, particularly when combined with problem-based or project-based learning activities during the in-class phase. This study recommends further empirical and comparative research to strengthen evidence of the model's effectiveness across diverse subjects and educational levels.